„Klatka bez drzwi i bez klucza”. Analiza aspektów poznawczych i etycznych wybranych przedstawień artystycznych niepełnosprawności i osób z niepełnosprawnościami - Zamojska, Eva (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The aim of my paper is to analyze cognitive and ethical aspects of selected literary and film depictions of disabilities. Based on theoretical and methodological assumptions of sociology of literature and critical discourse analysis I set out to demonstrate how selected literary and film works depict situations and problems with social inclusion of people with disabilities. I concentrate on two questions: 1) How do artistic creations build non-disabled people's knowledge of the social situation and position of people with disabilities? 2) What ethical problems can such depictions involve?